Uji Diagnostik Tes Cepat Molekuler Dalam Mendeteksi Bakteri Mycobacterium Tuberculosis Pada Pasien Tb Paru di RSUP H. Adam Malik Medan Tahun 2024 - Siahaan, Perry Boy Chandra; Firdauz, Firman; Fadillah, Mardi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Tuberculosis is an infectious disease caused by bacteria from the Mycobacterium group, namely Mycobacterium tuberculosis, which attacks the lungs. WHO recommends the use of Molecular Rapid Tests as an initial examination for the diagnosis of Tuberculosis in patients with Pulmonary TB. Molecular Rapid Test examination is a molecular examination with Nucleic Acid Amplification Technology (NAAT) technology that can diagnose TB and resistance to Rifampicin in less than 2 hours. This study aims to determine the diagnostic test of molecular rapid tests in detecting M. tuberculosis bacteria in TB patients at H. Adam Malik Hospital Medan. This research was conducted at the Microbiology Laboratory of H. Adam Malik Hospital Medan in June - August 2024, starting from literature search to writing research reports. The population in this study were all sputum patients with suspected pulmonary tuberculosis at H. Adam Malik Hospital Medan. The sampling technique is Total Sampling where the number of samples is equal to the number of pupulations, namely 108 patients in 2024. The results of the Molecular Rapid Test research obtained 105 people had positive results found Mycobacterium tuberculosis bacteria. Based on the percentage of the results of the Molecular Rapid Test, 105 people had positive results found Mycobacterium tuberculosis bacteria and 3 people had no Mycobacterium tuberculosis bacteria found. From these data, it can be seen that the sensitivity value of the Molecular Rapid Test tool is 97,2%. The conclusion of this study is that the molecular rapid test in detecting Mycobacterium tuberculosis bacteria can be used as a screening to diagnose TB disease.